Exploring yield gaps in smallholder oil palm production systems in eastern Sumatra, Indonesia. (July 2016) - Euler, Michael; Hoffmann, Munir P.; Fathoni, Zakky; Schwarze, Stefan
Abstract: Oil palm ( Elaeis guineensis ) has become the most important oil crop throughout the world. The growing palm oil production was mainly based on the expansion of cultivated area into forest areas, causing serious environmental and social concerns. Increasing yields on existing plantations is a potential pathway to reduce the undesired ecological impacts of oil palm agriculture while enhancing its social benefits. Although oil palm production is still dominated by large private estates, smallholder farmers are increasingly engaging in its cultivation. While there is some evidence that smallholders' palm oil yields show large variations and are often far below plantation standards, empirical studies on their agronomic performance are scarce. Based on crop modeling analysis and farm household survey data from Sumatra, Indonesia, this paper quantifies smallholder yield gaps relative to exploitable yield levels and analyses smallholders' production constraints. Results show that oil palm smallholdings offer a tremendous potential for future yield increases, because they obtain, on average, only around 50% of the cumulative exploitable yield over a 20 year plantation life cycle. In particular, we find yield gaps to be largest during the most productive phase of oil palm. Our results indicate that farmers do not adapt their labor and fertilizer inputs to the higher resource demand of the palm. In general, significant determinants of yield gaps are management practices such as fertilizer dosage, length of harvesting intervals and plant mortality. Supported smallholders perform relatively better compared to independent farmers. In summary, our study shows that there is large potential to increase productivity of smallholder oil palm systems in Sumatra. In order to exploit this opportunity, farmers' awareness about the changing management requirements of oil palm over the plantation life cycle needs to be enhanced. Highlights: There is a large potential to increase the productivity of smallholder oil palm systems in Sumatra. Production constraints include inadequate nutrient supply and harvesting frequency. Yield gaps are largest during the most productive phase of the oil palm plantation. Supported smallholders achieve higher yields compared to independent farmers. Adjustment of management to age specific requirements of oil palm may foster yields.